Management of children with hemophilia A on emicizumab who need surgery - Belletrutti, Mark; Bhatt, Mihir; Samji, Nasrin (Frontiers in Pediatrics, 2023)
The introduction of emicizumab into the treatment regime of persons with hemophilia A has dramatically reduced frequency of bleeding in patients with and without inhibitors. However, in children with Hemophilia A (CwHA) who require surgical or other invasive procedures, additional treatment with factor replacement or other hemostatic agents may still be needed to prevent intraoperative or postoperative bleeding. This review will look at the reported outcomes in CwHA on emicizumab who have had surgery and propose recommendations for the best perioperative management of major and minor procedures.